2015
DOI: 10.1002/wnan.1357
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐based imaging of inflammatory bowel disease

Abstract: Although inflammatory bowel disease (IBD) has been extensively studied, the pathogenesis is still not completely understood. As a result, the treatment options remain unsatisfactory and nonspecific. With the rapid advancement of diagnostic imaging techniques, imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) are playing a more important role in IBD diagnosis and evaluation. Recent developments in nanotechnology utilize an interdisciplinary approach to specifically target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 102 publications
(199 reference statements)
0
17
0
5
Order By: Relevance
“…Interestingly, TSPO is located and has similar expression characteristics in the enteric nervous system (Ostuni et al, ). One study has demonstrated TSPO ligand induced mitochondrial stabilization and ROS reduction in a mouse model of inflammatory bowel disease (Issop et al, ), while others demonstrate diffuse TSPO upregulation (Bernards et al, 2015; Wu, Briley, & Tao, ). Studies of the colon and brain have separately demonstrated the pivotal role NOX‐2 derived ROS has in inflammatory disease progression (Mouzaoui et al, ; Stolk et al, ; Marín et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TSPO is located and has similar expression characteristics in the enteric nervous system (Ostuni et al, ). One study has demonstrated TSPO ligand induced mitochondrial stabilization and ROS reduction in a mouse model of inflammatory bowel disease (Issop et al, ), while others demonstrate diffuse TSPO upregulation (Bernards et al, 2015; Wu, Briley, & Tao, ). Studies of the colon and brain have separately demonstrated the pivotal role NOX‐2 derived ROS has in inflammatory disease progression (Mouzaoui et al, ; Stolk et al, ; Marín et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A wide literature exists about the translational potential of nanotechnology in cancer or infectious diseases, but the application to IBD management has been poorly investigated. [36] In this study, we developed a targeted nanoplatform for early recognition of acute colitis. Our findings demonstrated that MAdCAM-1-targeted nanoparticles actively accumulated in inflamed bowel sites due to MAdCAM-1 overexpression in endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…It is very well to accept that nanoformulation has potential in modulating inflammation. Nanotherapeutics induced with the cell membranes of cells involved in the inflammatory progression more efficiently used for effective targeted transport to inflamed tissues 148 . The innovative technology is "nanotheranostics, “which crosses all the hurdles, not properly addressed in the development of nanomedicines and albeit with many limitations to overcome 149 , 150 .…”
Section: Discussionmentioning
confidence: 99%